Famílias e formação ética: a educação das crianças sob a ótica de mulheres - Alves, Maria Cherubina de Lima [UNESP] (2014)
In order to explain the role that family members perceive having in the ethical instruction of their children, in the city of Franca, an inner city in the state of São Paulo, this paper discusses the social institutions influences such as school and family in socialization, trying to analyze the ideological discourses contained in the family concepts and its social role. The ethical values apprehended by people have sociocultural and historical influences which are beyond the families' free choice and self-control, suffering a strong imposition of the neoliberal capitalist culture responsible for disseminating ethical values such as individualism, competitiveness, life human devaluation, inequality and social exclusion increasing. Families, regardless of their settings, together with educational institutions, have been charged for the set of values internalized by children and youths as well as for their consequential behaviors and choices. In a qualitative approach, this exploratory descriptive study used the dialectical method in the presentation and analysis of the studied subject. Five families users of the Unidade Auxiliar Centro Jurídico Social (Social Law Center Auxiliary Unit) participated in the survey, represented by seven adult women (since in two families, the mother and daughter attended the survey), aged from 28 to 62 years old with a household income from one to two and a half minimum wage. Semi-structured interviews conducted in the participants' home were made, observing ethical guidelines concerning with human research. The results were organized into thematic categories, formulated from the analysis of interviews, as follows: Authority, obedience and freedom of choice; Educating and being educated process; Socialization and technical training of children: the school; and Humanistic ethics values and Neoliberal ethics values. It was concluded that in our society coexist the...